2014
DOI: 10.5505/pajes.2014.08379
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution Algorithm Based Solution Approaches for Solving Transportation Network Design Problems

Abstract: GirişBirleştirilmiş Ulaşım Ağ Tasarımı (BUAT) problemi genel olarak bütçe kısıtları altında ulaşım ağında yapılabilecek en uygun iyileştirmelerin belirlenmesi olarak tanımlanabilir. BUAT problemi, Ayrık Ulaşım Ağ Tasarımı (AUAT) ve Sürekli Ulaşım Ağ Tasarımı (SUAT) problemlerinin birlikte göz önüne alınması ile ortaya çıkmıştır. Diğer bir deyişle BUAT probleminde ulaşım ağına eklenmesi düşünülen bağlar ve kapasite artırımına aday bağların belirlenmesi problemleri beraber ele alınmaktadır. Yerel idareciler ve u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition to this, the degree of saturation for each lane was constrained with a maximum of 1.2. Differential Evolution (DE) algorithm which is a powerful and simple meta-heuristic optimization algorithm is preferred to solve the signal timing optimization problem [45][46][47][48][49]. A signal timing optimization program was developed in MATLAB for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the degree of saturation for each lane was constrained with a maximum of 1.2. Differential Evolution (DE) algorithm which is a powerful and simple meta-heuristic optimization algorithm is preferred to solve the signal timing optimization problem [45][46][47][48][49]. A signal timing optimization program was developed in MATLAB for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In these scripts, MSE for observed and model data was minimized using the Differential Evolution Algorithm. Control parameters of the algorithm were selected considering the previous studies in the literature and were presented in Table 2 [22,36,37]. In the second step, each script was run ten times.…”
Section: Explicated Mathematical Modelmentioning
confidence: 99%
“…Genetic Algorithm (GA), Harmony Search Algorithm (HS), Particle Swarm Optimization Algorithm (PSO), Ant Colony Optimization Algorithm (ACO), Arti cial Bee Colony Algorithm (ABC), and Di erential Evolution (DE) are some of the most used metaheuristic optimization methods for the solution of the problems. Previous studies in the literature showed that more e ective solutions can be achieved by using the Di erential Evolution algorithm rather than the other metaheuristic optimization algorithms [33][34][35][36][37]. us, it is preferred in this study.…”
Section: Performance Criteriamentioning
confidence: 99%